How does negative new media coverage impact audit fees, cost cover, or risk premium? Based on the data from WeChat official account by Crawler Technology. - Tao Feng; Chuan Zhang; LiXia Liu; Xin Lin (PLoS ONE)
This study empirically investigates the relationship between negative new media coverage and audit fees by collecting a sample of nonfinancial listed companies on the main board of the Shanghai Stock Exchange (SSE) from 2017 to 2019, along with data on negative new media coverage of official WeChat public accounts founded by the most influential national financial newspaper obtained using a crawler. This study revealed that: 1. Audit fees are significantly and positively related to negative news media coverage; 2. The increase in audit fees is due to the fact that if a listed company undergoes negative new media coverage, the accounting firm that audits the company will consequently increase risk premium and thus audit fees. We found no evidence that accounting firms spend more time and effort on audit work after a listed company experiences negative new media coverage; 3. Analyst-tracking has a moderating effect on negative new media coverage and audit fees, leading to an increase in audit fees; 4. Negative media reporting on non-state-owned enterprises is more likely to cause accounting firms to increase their audit fees than their state-owned peers, whereas "non-Big Four" accounting firms are more likely to increase their audit fees for companies with negative new media reports. This study, based on the differing impacts of negative new media coverage, intended to unravel the intricate relationship between different types of negative new media coverage and audit fees, help understand the mechanism whereby negative reporting impacts audit fees, and provides a benchmark for the development of a feasible audit fee system.